Beyond rural urban: keeping up with changing realities - Garrett, James L. (International Food Policy Research Institute, 2005)
Policies built on presumptions of separateness or on traditional notions of urban and rural livelihoods diminish the possibilities for economic growth and poverty reduction. More effective policies will take the diversity of livelihoods along the continuum into account and also appreciate the differences among urban and rural areas and the links between them. Focusing on the connections between urban and rural areas can help to reframe our understanding of development in these areas. We can see that rural and urban lives and livelihood strategies span rural and urban geographies in integrated and interdependent ways.With better understanding of the current reality of urban and rural areas and the connections between them, policies will better reflect the ways people actually live. Policies will take into account the different livelihood strategies, links, and localities that exist across “urban” and “rural.” And they will be able to promote synergies—such as market exchange—that benefit all, no matter where they live.